2014
DOI: 10.4028/www.scientific.net/amm.706.81
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of Shrouded Turbine Blade System with Impact and Friction

Abstract: Dry friction dampers are passive devices used to reduce the resonant vibration amplitudes in turbine bladed systems. In shrouded turbine blade systems, in addition to the stick- slip motion induced by dry friction during the contact state in the tangential direction, the interface also undergoes intermittent separation in the normal direction. The problem can thus be treated as a combination of impact and friction. In this work, the dynamics of dry friction damped oscillators which are representative models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Each shroud keeps in touch with its adjacent ones. e dry friction model proposed by Santhosh et al [26] is applied, as shown in Figure 6. Contact of adjacent shrouds is regarded as a platform damper with a linear spring, whose stiffness is k s .…”
Section: Analysis Of Dry Friction Forces On Shroudmentioning
confidence: 99%
See 1 more Smart Citation
“…Each shroud keeps in touch with its adjacent ones. e dry friction model proposed by Santhosh et al [26] is applied, as shown in Figure 6. Contact of adjacent shrouds is regarded as a platform damper with a linear spring, whose stiffness is k s .…”
Section: Analysis Of Dry Friction Forces On Shroudmentioning
confidence: 99%
“…erefore, coupling force exists between tenons. ere is also dry friction force between adjacent shrouds, which is relative to the motion of their contact interfaces [8,19,[24][25][26]. ree sectors are selected to build a lumped parameter model of a bladed disk similar to that in [19], as shown in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
“…Based on lumped mass model, [7][8][9][10][11][12][13][14][15] some scholars have analyzed the nonlinear dynamic characteristics of vibroimpact system. Banerjee et al 7 studied the nonlinear grazing bifurcation characteristics of an impact system by experiment, and their results indicated that the narrow band of chaos could appear under the grazing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al 7 studied the nonlinear grazing bifurcation characteristics of an impact system by experiment, and their results indicated that the narrow band of chaos could appear under the grazing conditions. Santhosh et al 8 established a single degree of freedom (DOF) model under constant and variable normal loads to investigate the nonlinear dynamic phenomena of turbine shrouded blade with impact and friction. Jiang and Wiercigroch 9 investigated the grazing bifurcation characteristics of an oscillator with one-sided constraint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation